2006
DOI: 10.1196/annals.1386.029
|View full text |Cite
|
Sign up to set email alerts
|

HER2/neu Expression in Relation to Clinicopathologic Features of Breast Cancer Patients

Abstract: We have evaluated HER2/neu expression in 1,355 breast cancer patients recruited at the Breast Cancer Registry in Palermo between January 1999 and December 2004. In this retrospective study, HER2/neu expression was related to clinicopathologic features of the disease, including tumor size, nodal and menopausal status, estrogen and progesterone receptors. Statistical analysis on all 1,355 patients showed a significant correlation between HER2/neu and nodal status (P < 0.001), and a significant association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
4
15
1
Order By: Relevance
“…The signifi cance of amplifi ed oncogene in breast cancer has been the subject of debate. HER-2/neu(Cerb-B-2) is the gene known to show the highest frequency of amplifi cation, and has in several reports been associated with breast carcinoma progression and clinically aggressive behaviour of BC [22][23][24][25][26][27][28][29][30]. There was inverse relationship in between HER-2/neu over expression and ER/PR receptor status (table 4), similar observation also revealed by other studies [26,27].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The signifi cance of amplifi ed oncogene in breast cancer has been the subject of debate. HER-2/neu(Cerb-B-2) is the gene known to show the highest frequency of amplifi cation, and has in several reports been associated with breast carcinoma progression and clinically aggressive behaviour of BC [22][23][24][25][26][27][28][29][30]. There was inverse relationship in between HER-2/neu over expression and ER/PR receptor status (table 4), similar observation also revealed by other studies [26,27].…”
Section: Discussionsupporting
confidence: 73%
“…This indicates poor prognosis of our patients and this is again supported by lower hormone receptor expression on our patients which is 25-27% in comparison >50% in most western literature [26]. One possibility of difference in incidence of HER-2/neu could be because 1+ staining detected in immunohistochemical technique is regarded as negative by FISH technique, but many series are showing similar low incidence despite of not grading the stain.…”
Section: Discussionmentioning
confidence: 65%
“…This group appeared to represent an aggressive form of breast cancer, presenting at a younger age with large tumor size. Despite the great variation in levels of HER-2/neu positivity, nearly all investigators report a negative relationship between HER-2/neu status and steroid receptors levels [6,7,8,9] This inverse association has been linked to the fact that estrogens and its receptor are required to suppress HER-2. This leads to lower or absent hormone receptors in women with HER-2/neu positive breast cancers.…”
Section: Association Of Her-2/neu Receptor Status With Agementioning
confidence: 99%
“…Another study (Menard et al, 2002) found in 1,928 patients that tumor size (﹥2 cm) correlated closely with poor outcome of HER-2 overexprssed breast cancer. A third study (Traina et al, 2006) had the same conclusion from a study in 1,355 patients with early breast carcinoma. Our result was similar: patients with a tumor greater than 2 cm had significant reduction in OS (p=0.015) and DFS (p=0.019).…”
Section: Discussionmentioning
confidence: 52%